INDUSTRIALITATION EFFECTS IN GEORGE ORWELL’S THE ROAD TO WIGAN PIER (1937) - Afina Aji Bangkit; Yusup Jamaludin (Universitas Islam Negeri Sunan Gunung Djati, 2021)
To see industrialization effects in England, this research focused on a literary work of an essay. The book can describe and express what happened in the reality. This research focuses on the book to know Industrialization effects on George Orwell The Road to Wigan Pier. The Road to Wigan Pier written in 1937 tells the experience, notes, and ideas from George Orwell when he walked down the slums area in England. In order to reveal the ideology within the book, this research uses qualitative research to interpret the data. The data were collected through purposive sampling, namely focusing on the data that concerns the industrialization encountered in the elements of the book. As a result, George Orwell divided his work into two parts. The first part content about George Orwell notes when he walked down the slums area in England. He describes slums condition, the lodging that he occupies, the state of miners condition, poverty, and unemployment. In the second part content about George Orwell idea and his critic of industrialization effects and the failure of socialism and his perspective on socialism, his opinion about socialism that the real socialist is people who actively want to see tyranny is destroyed and not only imagine that matters only to want. Keywords: Industrialization; Industrialization effects; socialism